Integrated deep learning, growth mindset, and spirituality training for elementary teachers - Beny Al Fajar; Eddy Noviana; Otang Kurniaman; Radini; Zufriady (Jurusan Ilmu Pendidikan Fakultas Keguruan dan Ilmu Pendidikan Universitas Riau, 2025)
This community service program aimed to strengthen the pedagogical capacity of elementary-school teachers in the Rakit Kulim teacher cluster, Indragiri Hulu Regency, Riau Province, through an integrated training program on Deep Learning (Pembelajaran Mendalam), growth mindset, and teacher spirituality to foster a favorable classroom climate. Implemented on 22–23 August 2025 with 40 participants, the program combined short concept briefings, collaborative lesson-design clinics, microteaching, and reflective coaching. Participants developed lesson designs that are mindful, meaningful, and joyful, grounded in holistic development (mind–heart–sense–body) and a staged learning sequence (understanding, applying, and reflecting). Growth mindset practices were incorporated to encourage iterative improvement, while spirituality-informed culture building emphasized respectful language, empathy, and consistent classroom agreements. Key outputs included contextual topic maps, draft lesson designs aligned with the Deep Learning framework, an assessment portfolio (assessment as learning, for learning, and of learning), and a cluster-level follow-up plan for peer mentoring. Overall, the integrated approach suggests that teachers are better prepared to implement deeper, more humanizing learning in elementary classrooms.